THE IMAGE OF THE SOVIET WOMAN IN THE BOLSHEVIK’S TEXTS AND PROPAGANDA MATERIALS OF THE 1920S - K. R. Ambartsumyan; T. A. Bulygina (Гуманитарные и юридические исследования)
The author compares images of a “new woman” in the Bolshevik’s ideological narrative. The image under consideration was a part of a social project coined the “new man”. The works by Bolshevik leaders, including women (I. Armand, N. Krupskay, A. Kollontai), which conveyed certain characteristics of the ideal of a Soviet woman, were used in the study as sources. Modification of mentality, including the female one, according to V. Lenin’s plan was significant for practical reasons. It was suggested that women had to take a part in socialist building of a new society. All mentions of the need to emancipate women in his texts related to the goal of the current moment: industrial reconstruction, electrification, elimination of illiteracy, etc. Bolshevik women considered themselves as the active participants of revolutionary struggle («Proletarian of a later call»). They supposed woman had deserved the freedom by that struggle. A distinctive feature of the time was the propagandized defamilization of women, expressed in calls for liberation from domestic slavery. However, ideological attitudes were not implemented in real life. Analyzing the materials of the Ogonyok magazine, the author shows how theoretical attitudes and demonstrated practice correlated with each other. Biographies, short stories and photos published in the magazine were intended to demonstrate the effectiveness of the policy pursued. There were examples of women who made their careers as chairpersons of village councils, gubernial executive committees, etc. There were numerous publications representing the process of emancipation of the East women (mainly in the caucasus and central Asia). The novelty of the work lies in the identification of the heterogeneity of the «new woman» concept. The author proved that the formed image was influenced by personal experience and gender of the Bolshevik government representatives, while the propaganda materials in the Soviet press rather broadcast the image of a “Soviet woman,” who was not yet a mass phenomenon.